(untitled) (Journal of the College of Education for Women, 2025)
This This paper defines peer teaching as a teaching methodology in the context of ESL/EFL. It aims to demonstrate the relationship between the teacher and language learners in the classroom by overviewing the advantages, disadvantages, and challenges that washout peer teaching method effectively. The research study addresses Arthurson’s themes, which include teaching skills, learning skills, student engagement and motivation, communication skills, preparation, and group work activities. The qualitative study hypothesizes whether or not the themes of peer teaching are statistically significant. The research instrument conducts a questionnaire on a 5-point Likert scale to diagnose the descriptive data of peer teaching themes. Sixty-five EFL teachers from the University of Baghdad, University of Tikrit, and University of Soran in Iraq responded randomly. The findings of the quantitative research are of direct practical relevance. The peer teaching method applies to teaching skills (M = 3.58, SD = 1.027) and communication skills (M = 3.53, SD = 0.967) compared to the other themes. One-way ANOVA determines the statistical significance of the mean scores in the themes of peer teaching. Given this evidence, EFL teachers can track peer teaching because of its successful teaching outcome in teaching and communication skills to create a convenient environment for student interaction. The study suggests that novice teachers need to participate in extensive training courses in the future to ensure peer-teaching experience. It is crucial to investigate the learners’ viewpoints towards this teaching method to reach valuable outcomes regarding students’ experiences in EFL classrooms.